2022
DOI: 10.1016/j.neuron.2021.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Learning and attention increase visual response selectivity through distinct mechanisms

Abstract: Learning and attention increase visual response selectivity through distinct mechanismsHighlights d Learning and attention both enhance sensory processing at different timescales d The effects of learning and attention are uncorrelated at the single-cell level d Learning is driven by response suppression, attention by enhancement and suppression d Model with cell class-specific top-down inputs can account for effects of attention

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 73 publications
2
22
0
Order By: Relevance
“…Conversely, L2/3 SOM+ cells increase their response when passively viewing a familiar stimulus (Kato et al, 2015;Makino and Komiyama, 2015). These findings can change with the presence of reward, attention, or a task (Makino and Komiyama, 2015;Fiser et al, 2016;Henschke et al, 2020;Wang et al, 2020;Poort et al, 2021). These observations in L2/3 fit well with calcium imaging in V1 L4 for principal, PV+ and SOM+ neurons (Kim et al, 2020;Hayden et al, 2021).…”
Section: Passive Viewing: Evidence Outside Of the Standard Stimulus-selective Response Plasticity Paradigmsupporting
confidence: 66%
See 2 more Smart Citations
“…Conversely, L2/3 SOM+ cells increase their response when passively viewing a familiar stimulus (Kato et al, 2015;Makino and Komiyama, 2015). These findings can change with the presence of reward, attention, or a task (Makino and Komiyama, 2015;Fiser et al, 2016;Henschke et al, 2020;Wang et al, 2020;Poort et al, 2021). These observations in L2/3 fit well with calcium imaging in V1 L4 for principal, PV+ and SOM+ neurons (Kim et al, 2020;Hayden et al, 2021).…”
Section: Passive Viewing: Evidence Outside Of the Standard Stimulus-selective Response Plasticity Paradigmsupporting
confidence: 66%
“…However, a closer inspection of data in mouse V1 shows that, while many GABAergic neurons show no or limited orientation preference, many do have a moderate orientation preference (Kerlin et al, 2010;Ma et al, 2010;Makino and Komiyama, 2015). Learning, albeit rewarded, has also been shown to increase the stimulus selectivity of PV+ interneuron populations (Khan et al, 2018;Poort et al, 2021), and SRP experiments show that SOM+ interneurons can gain orientation selectivity simply by exposure to novel gratings of a single orientation (Hayden et al, 2021). Presumably this acquisition of selectivity reflects an increased response to a subset of excitatory inputs conveying information about the familiar stimulus.…”
Section: Stimulus-selective Response Plasticity Expression Involves Two Competing Populations Of Inhibitory Interneuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BCI task used in this study was multimodal in nature. To determine whether our results generalize to a single-modality task, we trained mice in a visual discrimination task in which it was previously established that V1 activity is required for improved behavioral performance 16 , 50 , 51 . Converging evidence indicates visual discrimination training enhances the neural representation of rewarded stimuli by increasing selectivity for the stimuli experienced during training 16 , 21 and in some cases improving response reliability 16 , and at the same time suppresses responses to non-relevant stimuli 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, one possibility is that L2/3 PNs in M1 encode reward signals during the naive stage, but after associative learning, they habituate and become unresponsive to the reward stimulus. In addition, in the sensory cortices, the flexibility to either respond to or ignore sensory stimuli is based on the stimulus’ behavioral relevance and is gated by local SOM-INs ( Kato et al, 2015 ; Makino and Komiyama, 2015 ; Poort et al, 2021 ). In line with these findings, we found that SOM-INs became more reliably responsive to both the CS and the reward with associative learning.…”
Section: Discussionmentioning
confidence: 99%